Clinical Profile and Outcome of Patients with Melioidosis- A Single Center Retrospective Study - Dhas C P, Clement Jenil; Chidambaram, Yoganathan; Abilash, Nekkanti; Alagesan, Murali (Jordan Medical Journal, 2025)
Objective: The objective of the study was to study the clinical profile, epidemiological profile, laboratory features, and outcomes among melioidosis patients. Methods: A retrospective observational study was conducted at a tertiary healthcare center and 30 patients diagnosed with melioidosis were included and their case records were retrieved. Data which included clinical profiles, laboratory details and health outcomes and follow up details were collected and analyzed. Results: All patients had a mean age of 49.93±12.79 years and included more male participants (86.67%). Abnormal SGPT, SGOT, GGT, and APT levels were also observed. Blood was the most common specimen used for diagnoses (83.3%) and most patients were diabetic (83.33%). Common symptoms included fever (93.33%) followed by breathlessness (43.33%) with lung involvement in 53.33% of patients. Of all patients, 26.67% were deceased over the course of the study. Conclusion: Abnormal liver function tests along with presence of symptoms of fever, lung involvement, and possible diabetic state can be indicated for diagnostic tests for melioidosis while meropenem, septran, and ceftazidime showed high sensitivity toward melioidosis isolates.